THE CRISIS OF HUMAN EXISTENCE IN KAFKA'S METAMORPHOSES DIRECTORATE OF THE FEDERAL MINISTRY OF EDUCATION IN ERBIL - Ahmad, Dhiya Ali (International Journal of Psychosocial Rehabilitation, 2020)
The paper investigates Franz Kafka' Metamorphoses (1915 ) which presents the reader with a case of failure that leads to death. This novel tells the story that embodies the crisis of human existence, and clearly indicates a division that occurs as a result of accumulations, separating consciousness and subconscious. In other words, the novels in its general content is based on the idea of misery, lack of hope, and life changing upside down, and with its protagonist, Gregor Samsa turning into an insect. The paper attempts to discuss the depth of the existential message that Kafka ideas which indicate that there is no benefit from human existence in its various manifestations, because it is nihilist, worthless, and meaningless.